BETWEEN THE IDEAL AND PRAGMATIC INTERESTS IN LOACH'S THE WIND THAT SHAKES THE BARLEY MOVIE (2007): A MARXIST CRITICISM - PERMANASARI, PRIHANA INDA (2011)
The study examines how the tension between the ideal and pragmatic interest's reflected in The Wind That Shakes The Barley movie, based on Marxist Criticism. The aim of the study is to analyze the movie in term of its structural elements based on the Marxist Criticism.This study belongs to qualitative study, In this method, there were two types of data source, which was used, namely primary data and secondary data sources. the primary data source and the object of the study was the movie The Wind That Shakes The Barley it self, meanwhile the secondary one was any literature related to this study. The writer collected the data from both primary and secondary data sources by taking notes from text and by capturing images for the image a sort of document as evidence. This study used library research to collect the data. Having analyzed this movie, the conclusions are as follows, first, based on the structural analysis. Ken Loach wants to show although independence is important to everybody it may have different meanings to different people. Second based on the Marxist analysis The Wind That Shakes The Barley movie describes the struggle of Ireland people in fighting for independence of State Ireland from State England.